Systematic Literature Review : Penerapan Metode Branch and Bound dalam Optimalisasi Produksi - Sherly Putri Revika; Jamiah Nurhakiki; Bulan Naysabilla; Siti Salamah Br Ginting (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study presents a Systematic Literature Review (SLR) focusing on the application of the Branch and Bound (B&B) method in production optimization. In modern industry, achieving operational efficiency and profitability is essential, yet optimization often yields fractional solutions that are unrealistic for indivisible entities. The Branch and Bound method, as part of Integer Programming, has proven effective in addressing these constraints by converting fractional solutions into optimal integer values. This SLR analyzed 12 scientific articles published between 2016 and 2024, sourced from databases such as Google Scholar, Scopus, and SINTA. The analysis reveals that B&B is widely utilized to maximize production profit across various sectors, including spring beds, woven fabrics, bread, and furniture, often formulated as Integer Linear Programming (ILP) problems. Furthermore, this method is also applied to minimize production time and determine the shortest routes. Overall, B&B is a flexible and efficient tool that assists companies in managing resources and achieving maximum profit with realistic integer solutions.